Surgical Stabilization of Rib Fractures: A Review of the Indications, Technique, and Outcomes - Taylor Raffa; Parker Chang; Babak Sarani; Susan Kartiko (Medical Research Archives, 2023)
Rib Fractures are a common injury in trauma patients and affect 10% of all injured patients who require admission to the hospital. Currently, there is no consensus on the most efficacious treatment for rib fractures with the debate comparing non-surgical versus surgical management. Medical management of rib fractures often requires admission to the intensive care unit with a focus on pain control to allow good pulmonary hygiene. Pain control involved a multimodal approach with current techniques including epidural anesthesia and paravertebral blocks. Although many patients recover with medical management alone, some patients may benefit from surgical stabilization of rib fractures as a means of augmenting pain control. Flail chest is the most evidence-based indication for surgical stabilization of rib fractures SSRF with many studies showing decreased days on mechanical ventilation, risk of pneumonia, intensive care unit length of stay, and hospital length of stay. Additionally, in patients with non-flail chest and ventilator dependent respiratory failure, surgical stabilization of rib fractures may provide an advantage over medical management for pain control. There are relatively few contraindications and complications associated with surgical stabilization of rib fractures. Therefore, with proper patient selection, surgical stabilization of rib fractures can improve outcomes in patients with rib fractures. Medical management with or without surgical intervention requires a multidisciplinary approach to prevent adverse clinical outcomes. Keywords: Surgical stabilization of rib fractures, rib plating, rib fracture, flail chest, non-flail chest Article Details How to Cite RAFFA, Taylor et al. Surgical Stabilization of Rib Fractures: A Review of the Indications, Technique, and Outcomes. Medical Research Archives, [S.l.], v. 11, n. 11, nov. 2023. ISSN 2375-1924. Available at: . Date accessed: 02 dec. 2023. doi: https://doi.org/10.18103/mra.v11i11.4694. ABNT APA BibTeX CBE EndNote - EndNote format (Macintosh & Windows) MLA ProCite - RIS format (Macintosh & Windows) RefWorks Reference Manager - RIS format (Windows only) Turabian Issue Vol 11 No 11 (2023): November Issue, Vol.11, Issue 11 Section Review Articles The Medical Research Archives grants authors the right to publish and reproduce the unrevised contribution in whole or in part at any time and in any form for any scholarly non-commercial purpose with the condition that all publications of the contribution include a full citation to the journal as published by the Medical Research Archives. References 1. Ziegler D, Agarwal N. The morbidity and mortality of rib fractures. The Journal of trauma. 1994;37(6):975-979. http://ovidsp.ovid.com.proxygw.wrlc.org/ovidweb.cgi?T=JS&NEWS=n&CSC=Y&PAGE=fulltext&D=ovft&AN=00005373-199412000-00018. doi: 10.1097/00005373-199412000-00018. 2. Pieracci FM, Lin Y, Rodil M, et al. A prospective, controlled clinical evaluation of surgical stabilization of severe rib fractures. The journal of trauma and acute care surgery. 2016;80(2):187-194. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/26595710. doi: 10.1097/TA.0000000000000925. 3. Bulger E, Arneson M, Mock C, Jurkovich G. Rib fractures in the elderly. The journal of trauma. 2000;48(6):1040-1047. http://ovidsp.ovid.com.proxygw.wrlc.org/ovidweb.cgi?T=JS&NEWS=n&CSC=Y&PAGE=fulltext&D=ovft&AN=00005373-200006000-00007. doi: 10.1097/00005373-200006000-00007. 4. Dehghan N, de Mestral C, McKee MD, Schemitsch EH, Nathens A. Flail chest injuries: A review of outcomes and treatment practices from the national trauma data bank. The journal of trauma and acute care surgery. 2014;76(2):462-468. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/24458051. doi: 10.1097/TA.0000000000000086. 5. Bemelman M, Poeze M, Blokhuis TJ, Leenen LPH. Historic overview of treatment techniques for rib fractures and flail chest. Eur J Trauma Emerg Surg. 2010;36(5):407-415. https://www.narcis.nl/publication/RecordID/oai:cris.maastrichtuniversity.nl:publications%2F6b366c43-4f8d-4464-90f7-23e6ea3aeb19. doi: 10.1007/s00068-010-0046-5. 6. Tanaka H, Yukioka T, Yamaguti Y, et al. Surgical stabilization of internal pneumatic stabilization? A prospective randomized study of management of severe flail chest patients. The journal of trauma. 2002;52(4):727-732. http://ovidsp.ovid.com.proxygw.wrlc.org/ovidweb.cgi?T=JS&NEWS=n&CSC=Y&PAGE=fulltext&D=ovft&AN=00005373-200204000-00020. doi: 10.1097/00005373-200204000-00020. 7. Pieracci FM, Schubl S, Gasparri M, et al. The chest wall injury society recommendations for reporting studies of surgical stabilization of rib fractures. Injury. 2021;52(6):1241-1250. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.injury.2021.02.032. doi: 10.1016/j.injury.2021.02.032. 8. Pieracci FM, Leasia K, Bauman Z, et al. A multicenter, prospective, controlled clinical trial of surgical stabilization of rib fractures in patients with severe, nonflail fracture patterns (chest wall injury society NONFLAIL). The journal of trauma and acute care surgery. 2020;88(2):249-257. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/31804414. doi: 10.1097/TA.0000000000002559. 9. Tignanelli CJ, Rix A, Napolitano LM, Hemmila MR, Ma S, Kummerfeld E. Association between adherence to evidence-based practices for treatment of patients with traumatic rib fractures and mortality rates among US trauma centers. JAMA Network Open. 2020;3(3):e201316. http://dx.doi.org.proxygw.wrlc.org/10.1001/jamanetworkopen.2020.1316. doi: 10.1001/jamanetworkopen.2020.1316. 10. Chapman BC, Herbert B, Rodil M, et al. RibScore: A novel radiographic score based on fracture pattern that predicts pneumonia, respiratory failure, and tracheostomy. The journal of trauma and acute care surgery. 2016;80(1):95-101. https://www.ncbi.nlm.nih.gov/pubmed/26683395. doi: 10.1097/TA.0000000000000867. 11. Chen J, MD, Jeremitsky E, MD, Philp F, MS, Fry W, MD, Smith RS, MD. A chest trauma scoring system to predict outcomes. Surgery. 2014;156(4):988-994. https://www.clinicalkey.es/playcontent/1-s2.0-S0039606014003845. doi: 10.1016/j.surg.2014.06.045. 12. Kyriakakis R, Johnson B, Krech L, et al. Planning for the worst: The impact of a comprehensive, risk associated treatment protocol on unanticipated ICU admissions in patients affected by rib fractures. The American journal of surgery. 2022;224(1):602-606. https://dx.doi.org/10.1016/j.amjsurg.2022.03.042. doi: 10.1016/j.amjsurg.2022.03.042. 13. Williamson F, Warren J, Cameron CM. Rib fractures in blunt chest trauma: Factors that influence daily patient controlled opiate use during acute care. Injury. 2022;53(1):145-151. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.injury.2021.08.029. doi: 10.1016/j.injury.2021.08.029. 14. Kay AB, White T, Baldwin M, Gardner S, Daley LM, Majercik S. Less is more: A multimodal pain management strategy is associated with reduced opioid use in hospitalized trauma patients. The Journal of surgical research. 2022;278:161-168. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.jss.2022.04.032. doi: 10.1016/j.jss.2022.04.032. 15. Hamrick KL, Beyer CA, Lee JA, Cocanour CS, Duby JJ. Multimodal analgesia and opioid use in critically ill trauma patients. Journal of the American College of Surgeons. 2019;228(5):769-775.e1. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.jamcollsurg.2019.01.020. doi: 10.1016/j.jamcollsurg.2019.01.020. 16. Burton SW, Riojas C, Gesin G, et al. Multimodal analgesia reduces opioid requirements in trauma patients with rib fractures. The journal of trauma and acute care surgery. 2022;92(3):588-596. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/34882599. doi: 10.1097/TA.0000000000003486. 17. Elia N, Lysakowski C, Tramèr M. Does multimodal analgesia with acetaminophen, nonsteroidal antiinflammatory drugs, or selective cyclooxygenase-2 inhibitors and patient-controlled analgesia morphine offer advantages over morphine alone?: Meta-analyses of randomized trials. Anesthesiology (Philadelphia). 2005;103(6):1296-1304. http://ovidsp.ovid.com.proxygw.wrlc.org/ovidweb.cgi?T=JS&NEWS=n&CSC=Y&PAGE=fulltext&D=ovft&AN=00000542-200512000-00025. doi: 10.1097/00000542-200512000-00025. 18. Walters MK, Farhat J, Bischoff J, Foss M, Evans C. Ketamine as an analgesic adjuvant in adult trauma intensive care unit patients with rib fracture. The Annals of pharmacotherapy. 2018;52(9):849-854. https://journals-sagepub-com.proxygw.wrlc.org/doi/full/10.1177/1060028018768451. doi: 10.1177/1060028018768451. 19. Carver TW, Kugler NW, Juul J, et al. Ketamine infusion for pain control in adult patients with multiple rib fractures: Results of a randomized control trial. The journal of trauma and acute care surgery. 2019;86(2):181-188. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/30376537. doi: 10.1097/TA.0000000000002103. 20. Dunn L, Durieux M. Perioperative use of intravenous lidocaine. Anesthesiology (Philadelphia). 2017;126(4):729-737. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/28114177. doi: 10.1097/ALN.0000000000001527. 21. Biella G, Sotgiu ML. Central effects of systemic lidocaine mediated by glycine spinal receptors: An iontophoretic study in the rat spinal cord. Brain research. 1993;603(2):201-206. https://dx-doi-org.proxygw.wrlc.org/10.1016/0006-8993(93)91238-N. doi: 10.1016/0006-8993(93)91238-N. 22. Sihoe ADL, Lee T, Wan IYP, Thung K, Yim APC. The use of gabapentin for post-operative and post-traumatic pain in thoracic surgery patients. Eur J Cardiothorac Surg. 2006;29(5):795-799. http://ejcts.ctsnetjournals.org/cgi/content/abstract/29/5/795. doi: 10.1016/j.ejcts.2006.02.020. 23. Turan A, white P, karamanliolu B, memis D, tadoan M, pamuku Z, yavuz E (2006) gabapentin: An alternative to the cyclooxygenase-2 inhibitors for perioperative pain management. anesthesia & analgesia 102:175-181. 24. Peng PW, Wijeysundera DN, Li CC. Use of gabapentin for perioperative pain control – a meta-analysis. Pain Research and Management. 2007;12(2):85-92. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/17505569. doi: 10.1155/2007/840572. 25. Moskowitz EE, Garabedian L, Hardin K, et al. A double-blind, randomized controlled trial of gabapentin vs. placebo for acute pain management in critically ill patients with rib fractures. Injury. 2018;49(9):1693-1698. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.injury.2018.06.002. doi: 10.1016/j.injury.2018.06.002. 26. Thiruvenkatarajan V, Cruz Eng H, Adhikary SD. An update on regional analgesia for rib fractures. Current opinion in anaesthesiology. 2018;31(5):601-607. https://www.ncbi.nlm.nih.gov/pubmed/30020155. doi: 10.1097/ACO.0000000000000637. 27. Galvagno J, Samuel Michael, Smith CE, Varon AJ, et al. Pain management for blunt thoracic trauma: A joint practice management guideline from the eastern association for the surgery of trauma and trauma anesthesiology society. The journal of trauma and acute care surgery. 2016;81(5):936-951. https://www.ncbi.nlm.nih.gov/pubmed/27533913. doi: 10.1097/TA.0000000000001209. 28. Witt CE, Bulger EM. Comprehensive approach to the management of the patient with multiple rib fractures: A review and introduction of a bundled rib fracture management protocol. Trauma Surgery & Acute Care Open. 2017;2(1):e000064. http://dx.doi.org.proxygw.wrlc.org/10.1136/tsaco-2016-000064. doi: 10.1136/tsaco-2016-000064. 29. Malekpour M, Hashmi A, Dove J, Torres D, Wild J. Analgesic choice in management of rib fractures: Paravertebral block or epidural analgesia? Anesthesia and analgesia. 2017;124(6):1906-1911. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/28525509. doi: 10.1213/ANE.0000000000002113. 30. Elsharkawy H, Pawa A, Mariano ER. Interfascial plane blocks: Back to basics. Obstetric anesthesia digest. 2019;39(1):52-53. http://ovidsp.ovid.com.proxygw.wrlc.org/ovidweb.cgi?T=JS&NEWS=n&CSC=Y&PAGE=fulltext&D=ovft&AN=00132582-201903000-00057. doi: 10.1097/01.aoa.0000552928.96744.71. 31. Sesperez J, Wilson S, Jalaludin B, Seger M, Sugrue M. Trauma case management and clinical pathways: Prospective evaluation of their effect on selected patient outcomes in five key trauma conditions. The Journal of Trauma: Injury, Infection, and Critical Care. 2001;50(4):643-649. http://ovidsp.ovid.com.proxygw.wrlc.org/ovidweb.cgi?T=JS&NEWS=n&CSC=Y&PAGE=fulltext&D=ovft&AN=00005373-200104000-00008. doi: 10.1097/00005373-200104000-00008. 32. Sahr SM, Webb ML, Renner CH, Sokol RK, Swegle JR. Implementation of a rib fracture triage protocol in elderly trauma patients. Journal of trauma nursing. 2013;20(4):172-175. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/24305076. doi: 10.1097/JTN.0000000000000008. 33. Todd SR, McNally MM, Holcomb JB, et al. A multidisciplinary clinical pathway decreases rib fracture–associated infectious morbidity and mortality in high-risk trauma patients. The American journal of surgery. 2006;192(6):806-811. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.amjsurg.2006.08.048. doi: 10.1016/j.amjsurg.2006.08.048. 34. Zhang L, Hu W, Cai Z, et al. Early mobilization of critically ill patients in the intensive care unit: A systematic review and meta-analysis. PLoS ONE. 2019;14(10):e0223185. https://www.ncbi.nlm.nih.gov/pubmed/31581205. doi: 10.1371/journal.pone.0223185. 35. Berry MJ, Morris PE. Early exercise rehabilitation of muscle weakness in acute respiratory failure patients. Exercise and sport sciences reviews. 2013;41(4):208-215. https://www.ncbi.nlm.nih.gov/pubmed/23873130. doi: 10.1097/JES.0b013e3182a4e67c. 36. Granetzny A, Abd El-Aal M, Emam E, Shalaby A, Boseila A. Surgical versus conservative treatment of flail chest. evaluation of the pulmonary status. Interactive cardiovascular and thoracic surgery. 2005;4(6):583-587. http://icvts.ctsnetjournals.org/cgi/content/abstract/4/6/583. doi: 10.1510/icvts.2005.111807. 37. Marasco, Silvana F., MSurg, FRACS, Davies, Andrew R., FRACP, FCICM, Cooper, Jamie, FRACP, FCICM, MD, et al. Prospective randomized controlled trial of operative rib fixation in traumatic flail chest. Journal of the American College of Surgeons. 2013;216(5):924-932. https://www-clinicalkey-es.proxygw.wrlc.org/playcontent/1-s2.0-S1072751512014299. doi: 10.1016/j.jamcollsurg.2012.12.024. 38. Tanaka H, Yukioka T, Yamaguti Y, et al. Surgical stabilization of internal pneumatic stabilization? A prospective randomized study of management of severe flail chest patients. The journal of trauma. 2002;52(4):727-732. http://ovidsp.ovid.com.proxygw.wrlc.org/ovidweb.cgi?T=JS&NEWS=n&CSC=Y&PAGE=fulltext&D=ovft&AN=00005373-200204000-00020. doi: 10.1097/00005373-200204000-00020. 39. Ahmed Z, Mohyuddin Z. Management of flail chest injury: Internal fixation versus endotracheal intubation and ventilation. The Journal of Thoracic and Cardiovascular Surgery. 1995;110(6):1676-1680. https://dx-doi-org.proxygw.wrlc.org/10.1016/S0022-5223(95)70030-7. doi: 10.1016/S0022-5223(95)70030-7. 40. Voggenreiter G, Neudeck F, Aufmkolk M, Obertacke U, Schmit-Neuerburg K. Operative chest wall stabilization in flail chest—outcomes of patients with or without pulmonary contusion. Journal of the American College of Surgeons. 1998;187(2):130-138. https://dx-doi-org.proxygw.wrlc.org/10.1016/S1072-7515(98)00142-2. doi: 10.1016/S1072-7515(98)00142-2. 41. Fitzpatrick DC, Denard PJ, Phelan D, Long WB, Madey SM, Bottlang M. Operative stabilization of flail chest injuries: Review of literature and fixation options. Eur J Trauma Emerg Surg. 2010;36(5):427-433. https://link-springer-com.proxygw.wrlc.org/article/10.1007/s00068-010-0027-8. doi: 10.1007/s00068-010-0027-8. 42. Granhed HP, Pazooki D. A feasibility study of 60 consecutive patients operated for unstable thoracic cage. Journal of Trauma Management & Outcomes. 2014;8(1):20. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/25642282. doi: 10.1186/s13032-014-0020-z. 43. Leinicke J, Elmore L, Freeman B, Colditz G. Operative management of rib fractures in the setting of flail chest: A systematic review and meta-analysis. Annals of surgery. 2013;258(6):914-921. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/23511840. doi: 10.1097/SLA.0b013e3182895bb0. 44. Marasco, Silvana F., MSurg, FRACS, Davies, Andrew R., FRACP, FCICM, Cooper, Jamie, FRACP, FCICM, MD, et al. Prospective randomized controlled trial of operative rib fixation in traumatic flail chest. Journal of the American College of Surgeons. 2013;216(5):924-932. https://www-clinicalkey-es.proxygw.wrlc.org/playcontent/1-s2.0-S1072751512014299. doi: 10.1016/j.jamcollsurg.2012.12.024. 45. Doben AR, MD, Eriksson, Evert A., MD, FACS, FCCP, Denlinger CE, MD, et al. Surgical rib fixation for flail chest deformity improves liberation from mechanical ventilation. Journal of critical care. 2014;29(1):139-143. https://www-clinicalkey-es.proxygw.wrlc.org/playcontent/1-s2.0-S0883944113002888. doi: 10.1016/j.jcrc.2013.08.003. 46. Khandelwal G, Mathur RK, Shukla S, Maheshwari A. A prospective single center study to assess the impact of surgical stabilization in patients with rib fracture. International Journal of Surgery. 2011;9(6):478-481._https://www-clinicalkey-es.proxygw.wrlc.org/playcontent/1-s2.0-S1743919111001051. doi: 10.1016/j.ijsu.2011.06.003. 47. Prins J, van Lieshout E, Ali-Osman F, et al. Outcome after surgical stabilization of rib fractures versus nonoperative treatment in patients with multiple rib fractures and moderate to severe traumatic brain injury (CWIS-TBI). The journal of trauma and acute care surgery. 2021;90(3):492-500. https://www.narcis.nl/publication/RecordID/oai:pure.eur.nl:publications%2F1484a1fe-ee48-495e-828e-7732a85dc6bd. doi: 10.1097/TA.0000000000002994. 48. Lardinois D, Krueger T, Dusmet M, Ghisletta N, Gugger M, Ris H-. Pulmonary function testing after operative stabilisation of the chest wall for flail chest. Eur J Cardiothorac Surg. 2001;20(3):496-501. http://ejcts.ctsnetjournals.org/cgi/content/abstract/20/3/496. doi: 10.1016/S1010-7940(01)00818-1. 49. Craxford S, Owyang D, Marson B, et al. Surgical management of rib fractures after blunt trauma: A systematic review and meta-analysis of randomised controlled trials. Annals of the Royal College of Surgeons of England. 2022;104(4):249-256. https://www.ncbi.nlm.nih.gov/pubmed/34928718. doi: 10.1308/rcsann.2021.0148. 50. Apampa AA, Ali A, Kadir B, Ahmed Z. Safety and effectiveness of surgical fixation versus non-surgical methods for the treatment of flail chest in adult populations: A systematic review and meta-analysis. Eur J Trauma Emerg Surg. 2022;48(2):1025-1034. https://link.springer.com/article/10.1007/s00068-021-01606-2. doi: 10.1007/s00068-021-01606-2. 51. Swart E, Laratta J, Slobogean G, Mehta S. Operative treatment of rib fractures in flail chest injuries: A meta-analysis and cost-effectiveness analysis. Journal of orthopaedic trauma. 2017;31(2):64-70. https://www.ncbi.nlm.nih.gov/pubmed/27984449. doi: 10.1097/BOT.0000000000000750. 52. Schulte K, Whitaker D, Attia R. In patients with acute flail chest does surgical rib fixation improve outcomes in terms of morbidity and mortality? Interactive cardiovascular and thoracic surgery. 2016;23(2):314-319. https://www.ncbi.nlm.nih.gov/pubmed/27073261. doi: 10.1093/icvts/ivw092. 53. Choi J, Gomez GI, Kaghazchi A, Borghi JA, Spain DA, Forrester JD. Surgical stabilization of rib fracture to mitigate pulmonary complication and mortality: A systematic review and bayesian meta-analysis. Journal of the American College of Surgeons. 2021;232(2):211-219.e2. https://dx.doi.org/10.1016/j.jamcollsurg.2020.10.022. doi: 10.1016/j.jamcollsurg.2020.10.022. 54. Slobogean, Gerard P., MD, MPH, FRCSC, MacPherson, Cailan Alexander, MD, MHSc, Sun T, BSc, Pelletier M, MD, Hameed, S. Morad, MD, MPH, FRCSC, FACS. Surgical fixation vs nonoperative management of flail chest: A meta-analysis. Journal of the American College of Surgeons. 2013;216(2):302-311.e1. https://www.clinicalkey.es/playcontent/1-s2.0-S1072751512012768. doi: 10.1016/j.jamcollsurg.2012.10.010. 55. Farquhar J, MD, Almahrabi Y, MD, Slobogean, Gerard, MD, MPH, et al. No benefit to surgical fixation of flail chest injuries compared with modern comprehensive management: Results of a retrospective cohort study. Canadian Journal of Surgery. 2016;59(5):299-303. https://www-clinicalkey-es.proxygw.wrlc.org/playcontent/1-s2.0-S0008428X1630248X. doi: 10.1503/cjs.000515. 56. DeFreest, Lori, M.D., Ph.D, Tafen M, M.D, Bhakta A, M.D, et al. Open reduction and internal fixation of rib fractures in polytrauma patients with flail chest. The American journal of surgery. 2016;211(4):761-767. https://www.clinicalkey.es/playcontent/1-s2.0-S0002961015300490. doi: 10.1016/j.amjsurg.2015.11.014. 57. Majercik, Sarah, M.D., M.B.A., F.A.C.S, Cannon Q, B.A, Granger, Steven R., M.D., F.A.C.S, VanBoerum, Don H., M.D., F.A.C.S, White, Thomas W., M.D., F.A.C.S. Long-term patient outcomes after surgical stabilization of rib fractures. The American journal of surgery. 2014;208(1):88-92. https://www-clinicalkey-es.proxygw.wrlc.org/playcontent/1-s2.0-S0002961014000129. doi: 10.1016/j.amjsurg.2013.08.051. 58. Van Wijck SFM, Pieracci FM, Smith EF, et al. Rib fixation in patients with severe rib fractures and pulmonary contusions: Is it safe? The journal of trauma and acute care surgery. 2022;93(6):721-726. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/36121283. doi: 10.1097/TA.0000000000003790. 59. Pulley BR, Taylor BC, Fowler TT, Dominguez N, Trinh TQ. Utility of three-dimensional computed tomography for the surgical management of rib fractures. The journal of trauma and acute care surgery. 2015;78(3):530-534. https://www.ncbi.nlm.nih.gov/pubmed/25710423. doi: 10.1097/TA.0000000000000563. 60. Fokin AA, Hus N, Wycech J, Rodriguez E, Puente I. Surgical stabilization of rib fractures: Indications, techniques, and pitfalls. JBJS essential surgical techniques. 2020;10(2):e0032. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/32944413. doi: 10.2106/JBJS.ST.19.00032. 61. Bauman ZM, Beard R, Cemaj S. When less is more: A minimally invasive, intrathoracic approach to surgical stabilization of rib fractures. Trauma case reports. 2021;32:100452. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.tcr.2021.100452. doi: 10.1016/j.tcr.2021.100452. 62. Tay-Lasso E, Alaniz L, Grant W, et al. Prospective single center paradigm shift of surgical stabilization of rib fractures with decreased length of stay and operative time with an intrathoracic approach. The journal of trauma and acute care surgery. 2022;Publish Ahead of Print. https://search-proquest-com.proxygw.wrlc.org/docview/2729514523. doi: 10.1097/TA.0000000000003811. 63. Junker MS, Kurjatko A, Hernandez MC, Heller SF, Kim BD, Schiller HJ. Salvage of rib stabilization hardware with antibiotic beads. The American journal of surgery. 2019;218(5):869-875. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.amjsurg.2019.02.032. doi: 10.1016/j.amjsurg.2019.02.032. 64. Thiels CA, Aho JM, Naik ND, et al. Infected hardware after surgical stabilization of rib fractures: Outcomes and management experience. The journal of trauma and acute care surgery. 2016;80(5):819-823. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/26891160. doi: 10.1097/TA.0000000000001005. 65. Sarani B, Allen R, Pieracci FM, et al. Characteristics of hardware failure in patients undergoing surgical stabilization of rib fractures: A chest wall injury society multicenter study. The journal of trauma and acute care surgery. 2019;87(6):1277-1281. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/31107433. doi: 10.1097/TA.0000000000002373. 66. Choi J, Gomez GI, Kaghazchi A, Borghi JA, Spain DA, Forrester JD. Surgical stabilization of rib fracture to mitigate pulmonary complication and mortality: A systematic review and bayesian meta-analysis. Journal of the American College of Surgeons. 2021;232(2):211-219.e2. https://dx-doi-org.proxygw.wrlc.org/10.1016/j.jamcollsurg.2020.10.022. doi: 10.1016/j.jamcollsurg.2020.10.022. 67. Beks RB, de Jong MB, Houwert RM, et al. Long-term follow-up after rib fixation for flail chest and multiple rib fractures. Eur J Trauma Emerg Surg. 2019;45(4):645-654. https://www.narcis.nl/publication/RecordID/oai:dspace.library.uu.nl:1874%2F394258. doi: 10.1007/s00068-018-1009-5. 68. Allen R, Estroff J, Sarani B. Surgical stabilization of rib fractures in a patient with empyema: A case report. JBJS Case Connector. 2019;9(4):e0202. https://www.ncbi.nlm.nih.gov/pubmed/31770114. doi: 10.2106/JBJS.CC.19.00202. 69. Ju T, Rivas L, Sarani B. Successful surgical stabilization of rib fractures despite candida colonization of the mediastinum. The Annals of thoracic surgery. 2018;106(3):e121-e123. https://dx.doi.org/10.1016/j.athoracsur.2018.03.009. doi: 10.1016/j.athoracsur.2018.03.009. 70. Pieracci FM, Majercik S, Ali-Osman F, et al. Consensus statement: Surgical stabilization of rib fractures rib fracture colloquium clinical practice guidelines. Injury. 2016;48(2):307-321. https://www-clinicalkey-es.proxygw.wrlc.org/playcontent/1-s2.0-S0020138316307665. doi: 10.1016/j.injury.2016.11.026. 71. Prins JTH, Van Lieshout EMM, Ali-Osman F, et al. Surgical stabilization versus nonoperative treatment for flail and non-flail rib fracture patterns in patients with traumatic brain injury. Eur J Trauma Emerg Surg. 2022;48(4):3327-3338. https://www.narcis.nl/publication/RecordID/oai:pure.eur.nl:publications%2Fde85bc10-e977-47be-b11e-c1a500d6f16b. doi: 10.1007/s00068-022-01906-1. 72. Wu T, Lin H, Chou Y, Huang F, Huang W, Tarng Y. Facilitating ventilator weaning through rib fixation combined with video-assisted thoracoscopic surgery in severe blunt chest injury with acute respiratory failure. Critical Care. 2020;24(1):49. https://www-ncbi-nlm-nih-gov.proxygw.wrlc.org/pubmed/32050985. doi: 10.1186/s13054-020-2755-4.